The Fiscal Cost of Conflict: Evidence from La Violencia in Colombia (2020)
This paper studies the effect of internal conflict on local fiscal capacity using evidence from Colombia's political confliict in the mid-20th century, better known as La Violencia. Following a difference-in-differences strategy, I find that internal conflict has negative long-term consequences in local fiscal capacity. More precisely, municipalities affected by La Violencia experienced an average reduction of 10.3% in their tax revenue and a fall of 2.8 percentage points on their ratio of taxes to total revenue. Effects lasted for more than a decade and are only partially explained by a population and economic activity downturn. These results are consistent with previous evidence indicating a negative effect of violence on tax collection efficiency at the local level.